Maximizing chickpea (Cicer arieitnum L.) productivity and profitability through customized fertilizers - Satya Narayan Meena; Preeti Verma; Suman Yadav; Chaman Jadon; Uditi Dhakad; S.N. Regar; M.L. Jat; Pratap Singh; L.K. Meena (Annals of Agricultural Research, 2023)
A field experiment was carried out during three consecutive rabi seasons (2019-20 to 2021-22) at Agricultural Research Station, Kota, Rajasthan to enhance the yield of chickpea through customized fertilizers. The experiment was laid out in Randomized Block Design comprising five treatments i.e., RDF (recommended level of N:P2 O:K2 O @ 20:40:20 kg/ha); RDF1 (Recommended level of N:P2 O:K2 O:S:ZnSO4:Na2 MoO4 @ 20:40:20:20:25:1 kg/ha- ); CFG1 (5.5:4.6:4.5:8.3:1.4:0.8:0.08:0.034 percent ratio of N:P:K:S:Zn:Fe:B:Mo) as per recommendation (100%) @ 100 kg/ha, CFG2 based on 75% recommendation @75 kg/ha and CFG3 based on 125% recommendation @ 125 kg/ha with four replication. The 3 years pooled data showed that among the different customized fertilizer grades (CFG) significantly higher plant height (68.7 cm), pods per plant (70.8), seed index (25.2 g), seed yield (2512 kg/ha), straw yield (4202 kg/ha), net returns (Rs. 101565/ha) and BC ratio (2.90) of chickpea was obtained with application of CFG3 (NPKSZnFeBMo) based on recommendation (125%) over the RDF (Recommended level of NPK) and CFG2 (NPKSZnFeBMo). Further data, revealed that CFG1 (NPKSZnFeBMo) based on recommendation (100%) and RDF1 (recommended level of NPK S Zn Mo) was recorded significantly higher growth and yield attributes, yield and economics of chickpea over RDF (Recommended level of NPK) and CFG2 (NPKSZnFeBMo) based on recommendation (75%).